Rutile-phased Titanium Dioxide (TiO2) Microstructures by Hydrothermal Method for Dye-Sensitized Solar Cell (DSSC) - I. M. Fazli, F.; M. Zaini, H.; K. Ahmad, M.; K. A. Hamed, N.; Nafarizal, N.; F. Soon, C.; Sanudin, R.; S. Aziz, H.; H. Mamat, M.; B. Suriani, A.; Shimomura, M.; Murakami, K. (International Journal of Engineering and Technology, 2019)
This paper presents rutile-phased titanium dioxide (TiO2) microstructures fabricated by hydrothermal synthesis for the application as a photoanode in DSSC. The amount of precursor, titanium (IV) butoxide (TBOT) was varied from 0.5 to 2 ml and the changes on the surface morphology, structural and electrical property as well as their performance in DSSC were evaluated by using FE-SEM, XRD, 4-point probeand solar simulator respectively. Since the amount of precursor is too low, no rods were able to grow from the FTO substrates used, but flower formations can be seen on sample with 2 ml of TBOT. The structural analysis revealed rutile spectra for all samples with the peaks gradually increased as the amount of precursor increased. The conductivity decreases as the film thickens with increasing precursor amount, while the resistivity and sheet resistance decreased as the amount increase; as rutile structure is known to have good electron mobility. The performance of the TiO2 films in DSSC was evaluated, and the sample with the best performance was found in the film with 2 ml TBOT precursor at 0.234 % with Jsc and Voc of 0.759 and 0.643 respectively. Increased TBOT precursor is concluded to increase the efficiency of DSSC but the limit is yet to be studied and further research will be needed.